Learning Models in the Laboratory and Simulator in Practical Learning in the Ship Engineering Study Program on the Quality of Learning - R. Bagus Wicaksono; Siswanto (International Journal of Science and Environment (IJSE), 2026)
This study aims to analyze the learning models in laboratories and simulators in practical learning of the Ship Machinery Study Program on the quality of learning at the Malahayati Maritime Polytechnic. This study uses a descriptive quantitative approach supported by qualitative data. The research subjects consisted of 50 cadets, 2 lecturers teaching the Construction and Working Principles of Refrigerator Auxiliary Machinery course, and the Head of the Ship Machinery Study Program as informants. Data were collected through questionnaires, observations, and interviews, then analyzed using frequency distribution and percentages. The results showed that the use of laboratories and simulators helped cadets understand auxiliary machinery systems on board ships, increased engagement in practical learning, and made the learning process more interesting. E-learning was also considered useful as a supporting medium because it facilitated the delivery of materials and communication between lecturers and cadets. However, this study found several obstacles, such as suboptimal laboratory and simulator features, unstable internet networks, limited free internet access, and less than optimal support for laboratory space and computer simulators. In addition, e-learning cannot replace direct practical learning because ship machinery competency requires real-life experience in laboratories and simulators. Thus, the most appropriate learning model is the integration between e-learning, laboratories, and simulators to support the quality of practical learning more effectively.